International core curriculum for capsule endoscopy training courses - Fernandez-Urien, I (2017)
Submitted by Helena Donato (bibliotecacuf@jmellosaude.pt) on 2017-06-25T20:20:44Z No. of bitstreams: 1 International core curriculum for capsule endoscopy training courses.pdf: 775298 bytes, checksum: 6ebf3e02fb7437367fcb3cdce17c83f9 (MD5)